DEVELOPMENT OF THE SMAILE GAME-BASED MEDIA TO ENHANCE SELF-LOVE AMONG SENIOR HIGH SCHOOL STUDENTS - Nurita, Sulis Dwi; Setyaputri, Nora Yuniar; Sancaya, Setya Adi (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
Self-love is a positive attitude toward oneself that can be learned and sustained throughout life. Observations at State Senior High School 3 Kediri revealed low levels of self-love among students, as indicated by behaviors such as self-harm, insecurity, and difficulty taking pride in themselves. These symptoms correspond to key indicators of self-love: self-awareness, self-worth, self-esteem, and self-care. To address this issue, this study aimed to develop a game-based counseling medium called Serenity Mahjong: Embracing Self-Love (SMAILE) as a tool for group counseling services. The research employed a Research and Development (R&D) approach using the ADDIE model. Instruments used included expert validation questionnaires, practicality questionnaires, and a self-love scale (pre-test and post-test). Validation results showed that the media was highly feasible and practical, with validation scores of 96.59% (media expert), 75% (content expert), and a practicality score of 91.67% from practitioners. Effectiveness testing using the Wilcoxon test indicated a significant increase in students' self-love scores after the intervention (p = 0.028). Therefore, the SMAILE media is proven to be valid, practical, and effective in enhancing students' self-love through group counseling services. It is recommended that the development of SMAILE be continued, with improvements in design, content, and activities tailored to students’ characteristics, and that broader trials be conducted to assess its wider applicability.